2016
DOI: 10.1021/acsami.6b05198
|View full text |Cite
|
Sign up to set email alerts
|

From Solution to Biointerface: Graphene Self-Assemblies of Varying Lateral Sizes and Surface Properties for Biofilm Control and Osteodifferentiation

Abstract: Bringing multifunctional graphene out of solution through facile self-assembly to form 2D surface nanostructures, with control over the lateral size and surface properties, would be an intriguing accomplishment, especially in biomedical fields where biointerfaces with functional diversity are in high demand. Guided by this goal, in this work, we built such graphene-based self-assemblies on orthopedic titanium, attempting to selectively regulate bacterial activities and osteoblastic functions, which are both cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
111
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 58 publications
5
111
0
Order By: Relevance
“…For instance, Chen et al described an osteogenic and antibacterial composite made of ZnO and carboxylated GO. [111] Bioactive and antibacterial properties of GMs and GM-based nanocomposites are also promising for dental applications. In another interesting recent study (Figure 6c), polydopamine-GO-coated Ti substrates were shown to have the capacity of triggering osteogenic differentiation (Figure 6d) and biofilm inhibition (Figure 6e) simultaneously.…”
Section: Functionalization Of Medical Device Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Chen et al described an osteogenic and antibacterial composite made of ZnO and carboxylated GO. [111] Bioactive and antibacterial properties of GMs and GM-based nanocomposites are also promising for dental applications. In another interesting recent study (Figure 6c), polydopamine-GO-coated Ti substrates were shown to have the capacity of triggering osteogenic differentiation (Figure 6d) and biofilm inhibition (Figure 6e) simultaneously.…”
Section: Functionalization Of Medical Device Surfacesmentioning
confidence: 99%
“…[117] They found that GO coatings can reduce the bacterial adhesion significantly (64% and 85% for S. aureus and P. aeruginosa, respectively) together with platelet adhesion reduction. [111] Copyright 2016, American Chemical Society. Podila et al have demonstrated that GM-coated nitinol surfaces show lower blood clotting (thrombosis) rate due to greater affinity of GMs toward albumin than fibrinogen.…”
Section: Functionalization Of Medical Device Surfacesmentioning
confidence: 99%
“…For antibacterial assays, TS, TS-M and TS-M/P/V (50 ÎŒg mL −1 ) samples were incubated respectively with 1 mL of bacterial suspensions at a concentration of 10 8 CFU mL −1 per well for 4 and 24 h. The antibacterial rates (Ra) of different samples against planktonic (Rap) and adhered (Raa) bacteria were quantitatively evaluated using a Microbial Viability Assay Kit-WST (Dojindo, Japan) according to the manufacturer's directions, which can calorimetrically detect bacteria metabolic activities that correspond well with the living bacterial amounts [34]. Briefly, at the end of incubation, the remaining culture media were collected, and the scaffolds were rinsed thoroughly to remove the none-adherent bacteria.…”
Section: Antibacterial Assaysmentioning
confidence: 99%
“…Interestingly, dopamine is capable of adaptively forming crosslinked strongly adhesive PD nanolayer onto virtually any substrate of any material/ shape at alkaline conditions, proving an advantageous platform for diverse surface design of biomaterials [32,33]. PD is rich in reactive quinone, carboxy, amino, imine, and phenol groups [34]. In particular, because of the coupling between the amine groups of heparin and quinone species in PD, heparin have been covalently immobilized onto various PD-modified substrates [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…These abundant epoxide, hydroxyl, and carboxylic groups on the GO basal plane and edges provide enormous reactive sites for chemical functionalization, which can substantially improve its interplay with proteins through hydrophobic and electrostatic interactions, and contribute to potentially enhance the osteogenic differentiation of stem cells . Furthermore, GO nanosheets display apparent antimicrobial capabilities for Gram‐negative and Gram‐positive bacteria . Hence, GO has been widely applied in various biotechnologies and biomedical applications such as biosensor, cellular imaging, nanoprobe, drug delivery, and tissue engineering .…”
Section: Introductionmentioning
confidence: 99%